2018
DOI: 10.1016/j.jmmm.2018.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the structural and magnetic properties of Co-Zn nanosized ferrites for hyperthermia applications

Abstract: A comparative study of the magnetic properties (magnetic moment, magnetocrystalline anisotropy) and hyperthermia response in Co-Zn spinel nanoparticles is presented. The CoxZn1-xFe2O4 nanoparticles (x = 1, 0.5, 0.4, 0.3, 0.2 and 0.1) were synthesized by co-precipitated method and the morphology and mean crystallite size (around 10 nm) of the nanoparticles were analysed by TEM Microscopy. Regarding the magnetic characterization (SQUID magnetometry), Co-Zn nanoparticles display at room temperature anhysteretic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 51 publications
1
13
1
2
Order By: Relevance
“…They reported a ferromagnetic order at room temperature for all samples with an improvement in coercivity and saturation magnetization by increasing the concentration of Co 2+ in the host structure. These results contradict other findings obtained by Gomea-Polo et al [29], who investigated the same nanoferrite system prepared by the co-precipitation method. Their structure and magnetic study indicated that the particle size increases from 9.4 nm to 14.7 nm with the increase of the Co 2+ content from 0.1 to 1.0, with superparamagnetic behavior at room temperature.…”
Section: Introductioncontrasting
confidence: 99%
“…They reported a ferromagnetic order at room temperature for all samples with an improvement in coercivity and saturation magnetization by increasing the concentration of Co 2+ in the host structure. These results contradict other findings obtained by Gomea-Polo et al [29], who investigated the same nanoferrite system prepared by the co-precipitation method. Their structure and magnetic study indicated that the particle size increases from 9.4 nm to 14.7 nm with the increase of the Co 2+ content from 0.1 to 1.0, with superparamagnetic behavior at room temperature.…”
Section: Introductioncontrasting
confidence: 99%
“…This value is also affected due to antiferromagnetic order between magnetic cations in B sites since the B-B super-exchange interactions become more significant because of the breaking of the dominant A-B interactions. Spin canting arises when in B-sites concentration of non-magnetic ions becomes too high and can be explained in the frame of the Yafet-Kittel model [27,32,34]. Gómez-Polo and colleagues observed a divergence of the calculated value of magnetic moment by measured value of inversion degree by neutron diffraction which was enhanced when the concentration of zinc increased [34].…”
Section: Chemical Control Of Magnetic Propertiesmentioning
confidence: 99%
“…Spin canting arises when in B-sites concentration of non-magnetic ions becomes too high and can be explained in the frame of the Yafet-Kittel model [27,32,34]. Gómez-Polo and colleagues observed a divergence of the calculated value of magnetic moment by measured value of inversion degree by neutron diffraction which was enhanced when the concentration of zinc increased [34]. In our case trend becomes more pronounced in the region of 0.25 < x < 1 because of the change of the slope in the linear fitting of this region (4 − 3.6 x) × µ B .…”
Section: Chemical Control Of Magnetic Propertiesmentioning
confidence: 99%
“…Different strategies have been adopted to tune hysteresis properties with the aim of increasing the relative heating contribution. A possible way is to use materials with high saturation magnetization and/or high uniaxial magneto-crystalline anisotropy, like cobalt or cobalt-zinc ferrites 19,2226 . Another strategy consists in modifying nanostructure geometry, introducing shape anisotropies; promising results were obtained with magnetite nanorods 27 , maghemite, magnetite or cobalt ferrite nanocubes 2830 and octahedral magnetite nanoparticles 31 .…”
Section: Introductionmentioning
confidence: 99%